DOES DISABILITY STATUS AFFECT MATERNAL CARE AROUND PREGNANCY? EVIDENCE FROM NATIONAL SURVEY OF FAMILY GROWTH (NSFG) 2013-2015 DATA IN UNITED STATES - Munir AHMED (Rojan GÜMÜŞ, 2020)
Introduction It is estimated that approximately 12% of the reproductive age women have some kind of disability; which is measured as self-reported difficulty in performing basic functions concerning movement, vision, hearing or cognition. Little research has been conducted on reproductive health of women with disabilities using nationally representative survey data; thus body of scientific knowledge on this subject is limited. Objectives The purpose of this study was to examine the effect of disability status (both mental and physical) among women on prenatal care and post-pregnancy care in U.S. using nationally representative National Survey of Family Growth (NSFG) data. Study design It's a retrospective, quantitative, observational study. Methods The 2013-2015 NSFG's female respondent file contains 5699 records one for each woman interviewed whereas the pregnancy respondent file contains 9358 records each related to a pregnancy. The data about disabilities related variables was part of female respondent file therefore using unique respondent ID files were merged and logistic regression models were built using prenatal and postnatal care as dependent and disability status as main independent variable. Results Women with Medicaid were significantly less likely as compared to those with private insurance to have received prenatal care in last 12 months. Women with less than 12 years education were less likely to have received post pregnancy care as compared to those with college education. Conclusion: Although this study did not find significant effects of disability on utilization of prenatal and post-pregnancy care, further research is needed on this subject with datasets that include comprehensive information about broader spectrum of disability status of women.